Comparative Analysis Of Mahmudkhoja Behbudiy’s Work “A Brief History Of Islam” - Khudoyberdiyev Rashid Zokirovich; Qutbiyeva Nargiza Zikriddin qizi (Zien Journals, 2025)
This article analyzes the content, historical significance, and comparative aspects of Mahmudkhoja Behbudiy’s work “A Brief History of Islam.” The study examines the author’s religiouseducational approach, his method of presenting Islamic history in a simple and accessible language, as well as his innovative role in conveying religious history to the public on a scientific basis. Through comparative analysis, the article identifies the place of Behbudiy’s work in the Islamic thought of his time and highlights its methodological and conceptual differences from the writings of historians such as al-Tabari, Jurjani, Ibn al-Athir, and Ahmad Donish
Keywords: Mahmudkhoja Behbudiy; A Brief History of Islam; Jadidism